Risk of depression after diagnostic prostate cancer workup – A nationwide, registry‐based study. Issue 11 (20th July 2021) - Friberg, Anne Sofie; Brasso, Klaus; Larsen, Signe Benzon; Andersen, Elisabeth Wreford; Krøyer, Anja; Helgstrand, John Thomas; Røder, Martin Andreas; Klemann, Nina; Kessing, Lars Vedel; Johansen, Christoffer; Dalton, Susanne Oksbjerg
Abstract: Objective: To compare the risk of depression after diagnostic workup for prostate cancer (PCa), regardless of the histopathologic outcome, with that of a cancer‐free population. Methods: A nationwide cohort of Danish men who had a prostatic biopsy sample in 1998–2011 was identified from the Danish Prostate Cancer Registry and compared to an age‐matched cohort from the background population. Men with other cancers, major psychiatric disorder, or prior use of antidepressants were excluded. The risk of depression defined as hospital contact for depression or prescription for antidepressants was determined from cumulative incidence functions and multivariate Cox regression models. Results: Of 54, 766 men who underwent diagnostic workup for PCa, benign results were found for 21, 418 and PCa was diagnosed in 33, 347. During up to 18 years of follow‐up, the adjusted hazard of depression was higher in men with PCa than in the background population, with the highest risk in the two years after diagnosis (hazard ratio (HR) 2.77, 95% CI 2.66–2.87). Comorbidity and lowest or highest income were significant risk factors for depression and the cumulative incidence was substantially higher in men with metastatic or high‐risk disease. In men with benign histopathology the HR for depression was 1.22 (95% CI 1.14–1.31) in the first two years but no different from the background population after that. Conclusions: Diagnostic workup for PCa is associated with an increased risk of depression, mainly among men with a diagnosis of PCa. Clinicians should be aware of depressive symptoms in prostate cancer patients.